Wolbachia Inter-Strain Competition and Inhibition of Expression of Cytoplasmic Incompatibility in Mosquito - Liang, Xiao; Liu, Julian; Bian, Guowu; Xi, Zhiyong (Frontiers in Microbiology, 2020)
Successful field trials have been reported as part of the effort to develop the maternally transmitted endosymbiontic bacteria Wolbachia as an intervention agent for controlling mosquito vectors and their transmitted diseases. In order to further improve this novel intervention, artificially transinfected mosquitoes must be optimized to display maximum pathogen blocking, the desired cytoplasmic incompatibility (CI) pattern, and the lowest possible fitness cost. Achieving such optimization, however, requires a better understanding of the interactions between the host and various Wolbabachia strains and their combinations. Here, we transferred the Wolbachia wMel strain by embryonic microinjection into Aedes albopictus, resulting in the successful establishment of a transinfected line, HM (wAlbAwAlbBwMel), with a triple-strain infection comprising wMel, wAlbA, and wAlbB. Surprisingly, no CI was induced when the triply infected males were crossed with the wild-type GUA females or with another triply infected HC females carrying wPip, wAlbA, and wAlbB, but specific removal of wAlbA from the HM (wAlbAwAlbBwMel) line resulted in the expression of CI after crosses with lines infected by either one, two, or three strains of Wolbachia. The transinfected line showed perfect maternal transmission of the triple infection, with fluctuating egg hatch rates that improved to normal levels after repeated outcrosses with GUA line. Strain-specific qPCR assays showed that wMel and wAlbB were present at the highest densities in the ovaries and midguts, respectively, of the HM (wAlbAwAlbBwMel) mosquitoes. These finding suggest that introducing a novel strain of Wolbachia into a Wolbachia-infected host may result in complicated interactions between Wolbachia and the host and between the various Wolbachia strains, with competition likely to occur between strains in the same supergroup.